2011
DOI: 10.1007/s10847-011-0003-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hydroxypropyl-β-cyclodextrin complexation on the aqueous solubility, structure, thermal stability, antioxidant activity, and tyrosinase inhibition of paeonol

Abstract: The objective of this paper is to study the effect of hydroxypropyl-b-cyclodextrin (HP-b-CD) complexation on the aqueous solubility, structure, thermal stability, antioxidant activity, and tyrosinase inhibition of paeonol (PAE). The inclusion complex (PAE-HP-b-CD complex) of HP-b-CD and PAE was prepared by a freeze-drying method. Phase solubility tests showed that the stability constant of the inclusion complex was about 33.8 M -1 at 25°C. The experimental results of proton nuclear magnetic resonance (H-NMR) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
7
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 36 publications
4
7
0
1
Order By: Relevance
“…The NS–TCF thermogram shows weight loss at 185 °C, corresponding to the degradation of TCF. These results are in agreement with the literature, suggesting that encapsulation improves the thermal stability of the guests [20,21,22,23,24,25,26,27].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The NS–TCF thermogram shows weight loss at 185 °C, corresponding to the degradation of TCF. These results are in agreement with the literature, suggesting that encapsulation improves the thermal stability of the guests [20,21,22,23,24,25,26,27].…”
Section: Resultssupporting
confidence: 93%
“…Figure 2 shows the XRPD patterns of the pesticide-loaded NS. In both diffraction patterns, the characteristic peaks of the pesticide were reduced [20,21,22,23,24,25,26,27]. It is also possible to confirm the lack of native NS and β-CD in the inclusion compound.…”
Section: Resultsmentioning
confidence: 92%
“…So, it is concluded that the thermal stability of GA did not alter by complexation in contrast to GA/HPβCD-PM. The observed results further confirm the complex formation [45]. In addition, the amount of GA in GA/HPβCD-IC and GA/HPβCD-PM were determined as ∼ 10.2 % and ∼ 9.4% from TGA thermogram, respectively.…”
Section: Thermal Analysis Of Inclusion Complexsupporting
confidence: 77%
“…3(a). The proton resonances of HP-␤-CD were assigned on the basis of findings from previous studies (Axel Castelli et al, 2008;Rezende et al, 2009;Tsao Fig. 1(b), in the range 3.85-4.10 ppm were those of H3 and H8, those in the range 3.50-3.75 ppm were those of H2, H4, and H7, and those in the range 3.70-3.85 ppm were those of H5 and H6.…”
Section: H Nmr Spectroscopic Analysismentioning
confidence: 99%